2017
DOI: 10.4236/ojas.2017.72009
|View full text |Cite
|
Sign up to set email alerts
|

Performance, Immune, and Carcass Characteristics of Broiler Chickens as Affected by Thyme and Licorice or Enzyme Supplemented Diets

Abstract: Numbers of 300 day-old broiler chickens through a CRD design with 5 treatments, 3 replicates and 20 chicks in each pen were used to evaluate the effect of thyme (T), licorice (L), thyme + licorice (TL), and enzyme supplemented (E) diets on performance, immune and carcass characteristics. According to the results, performance traits, immune indices, and carcass traits in herbal medicine and enzyme supplemented diets were improved significantly than control diet (P < 0.05). Weight gain and FCR in T and E groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
1
6
0
Order By: Relevance
“…Notably, the addition of licorice in broiler diets improved the weight of immune organs, such as the spleen or bursa, thereby promoting immune efficacy and the situation of livability and health [32]. Glycyrrhetinic acid has several favourable pharmacological properties, such as immunomodulation and production of interleukins [1,2,12] with subsequent production of antibodies, gamma interferon, and T-cells, which indicates its antiviral activity [33].…”
Section: Beneficial Role Of Licoricementioning
confidence: 99%
“…Notably, the addition of licorice in broiler diets improved the weight of immune organs, such as the spleen or bursa, thereby promoting immune efficacy and the situation of livability and health [32]. Glycyrrhetinic acid has several favourable pharmacological properties, such as immunomodulation and production of interleukins [1,2,12] with subsequent production of antibodies, gamma interferon, and T-cells, which indicates its antiviral activity [33].…”
Section: Beneficial Role Of Licoricementioning
confidence: 99%
“…Conversely Zhu et al [32] found no effect of thyme oil on the feed intake of Luhua chickens, but the growth rate of the chickens was increased when adding thyme oil. Kalantar et al [33] reported improvements in feed efficiency with thyme, including benefits in dressing weight. Zhu et al failed to find any effect on dressing % [32].…”
Section: Feed Intake and Growthmentioning
confidence: 99%
“…From these seven treatment groups, 1 bird/replicate was used for blood sampling, for immunity parameters a different bird was used from each replicate, and for carcass samples yet another bird was used from each replicate. The birds in the control group were given the basal diet, while those in treatment groups were given supplements as detailed below: Treatment 1: Basal diet (control); T1: Basal diet + thyme powder at 1% from days 29-42 T2: Basal diet + thyme powder at 2% from days 29-42 T3: Basal diet + thyme powder at 3% from days 29-42 S1: Basal diet + sumac powder at 1% from days 29-42 S2: Basal diet + sumac powder at 2% from days 29-42 S3: Basal diet + sumac powder at 3% from days [29][30][31][32][33][34][35][36][37][38][39][40][41][42] The basal diet consisted of a three-phase feeding program: starter feed from d 1-7, grower feed from d 8-24, and finisher feed from d [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The ingredients and nutrient composition of the diets are shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Glycyrrhizin (Gly) is found in various parts of licorice, but the roots contain most of the compound (Fiore et al, 2005). Licorice root is also known to have several pharmacological actions, including anti-in ammatory effects (Paudel et al, 2020), antibacterial properties (Rahnama et al, 2013), increased e ciency of the immune system (Kalantar et al, 2017), and reduction of blood cholesterol levels (Aghdam Shahryar et al, 2018). The use of glycyrrhizic acid in broiler chickens showed that these chickens had a higher body weight and better FCR than the control group (Ocampo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%